Perineal Groove: A Rare Congenital Midline Defect of Perineum - Mimily Harsono; Massroor Pourcyrous (Thieme Medical Publishers, Inc., 2016)
Abstract Perineal groove is a rare congenital malformation that is characterized by an exposed wet sulcus with nonkeratinized mucous membrane that extends from the posterior vaginal fourchette to the anterior ridge of the anal orifice. This condition is one of the uncommon anomalies of urogenital/anogenital region that is unknown to many clinicians. Although, this condition may be self-resolved before the age of 2 years, this nonepithelized mucous membrane can pose the risk of local irritation and infection, urinary tract infection, and the possibility of nonself-resolved condition that eventually needs surgical correction. Only a few reported cases (n = 23) were found in current medical literatures. This lesion could be misdiagnosed as contact dermatitis, trauma, or even sexual abuse. Therefore, recognition of the congenital perineal groove at birth is important for the health care providers to deliver an appropriate parental counseling and appropriate follow-up.